2021
DOI: 10.1093/occmed/kqab055
|View full text |Cite
|
Sign up to set email alerts
|

HSE Management Standards and burnout dimensions among rehabilitation professionals

Abstract: Background The Health & Safety Executive Indicator Tool (HSE-IT) is a standard-based questionnaire commonly used to assess work-related stress in organizations. Although the HSE-IT validity has been well documented and significant relationships have been observed between its scales and several work-related outcomes, to date there is no evidence concerning the relationships between the HSE-IT and burnout among healthcare workers. Aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The MS encompass the key six areas widely recognized as potential causes of work-related stress: (1) Demands : workload, company requirements, and task assignments; (2) Control : the perceived control of organizing and managing one’s own job activities; (3) Support : the level of encouragement, sponsorship, and resources provided by the organization, line management, and work colleagues; (4) Relationships : promoting good atmosphere at work to prevent interpersonal conflicts and deal with unacceptable behaviors; (5) Role : whether people understand their role and responsibilities within the organization and whether the organization ensures that the employees do not have conflicting roles; and (6) Change : how organizational change is managed and communicated within the organization. Based on this standard-oriented model, the same agency [ 15 , 16 ] developed the Health and Safety Executive Management Standards Indicator Tool (HSE-MS IT), which has been widely used in research on work-related stress [ 16 18 ].…”
Section: Measuring Multiple Work-related Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MS encompass the key six areas widely recognized as potential causes of work-related stress: (1) Demands : workload, company requirements, and task assignments; (2) Control : the perceived control of organizing and managing one’s own job activities; (3) Support : the level of encouragement, sponsorship, and resources provided by the organization, line management, and work colleagues; (4) Relationships : promoting good atmosphere at work to prevent interpersonal conflicts and deal with unacceptable behaviors; (5) Role : whether people understand their role and responsibilities within the organization and whether the organization ensures that the employees do not have conflicting roles; and (6) Change : how organizational change is managed and communicated within the organization. Based on this standard-oriented model, the same agency [ 15 , 16 ] developed the Health and Safety Executive Management Standards Indicator Tool (HSE-MS IT), which has been widely used in research on work-related stress [ 16 18 ].…”
Section: Measuring Multiple Work-related Stressorsmentioning
confidence: 99%
“…Most studies using the HSE-MS IT in healthcare settings have explored each potential source of stress separately, in this way missing potentially meaningful information on the patterns of work-related stress in distinct subgroups of healthcare workers [ 18 , 21 , 22 ]. One of the exceptions is the study by Portoghese et al [ 23 ], carried out among 1,671 healthcare workers in Italy, in which the person-centered approach was used to identify patterns of job types.…”
Section: Aim Of the Studymentioning
confidence: 99%
“…This systemic approach to well-being aligns with the core principles advocated in occupational health psychology, which predicates a principal focus on primary interventions to alleviate antecedents of work-related stress. For example, the UK Health and Safety Executive's (HSE) Management Standards approach (HSE, 2019), which was developed to help organisations assess and manage six work-related hazards of job demands, control, support, relationships, role, and change, has been found useful in tackling workplace stress in high-pressured occupations, such as health and social services (Carpi et al, 2021;Kerr et al, 2009).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Researchers confirm the existence of occupational burnout and a high risk of its occurrence [2,[10][11][12][13][14][15]. The studies carried out by Carpi et al and Durand et al demonstrated that 14% and 19.3% of the employees, respectively, were exposed to a high risk of occupational burnout [16,17]. Baudry et al found a high risk of burnout in 25% of participants [18].…”
Section: Introductionmentioning
confidence: 99%